Ephedrae Herba polysaccharides inhibit the inflammation of ovalbumin induced asthma by regulating Th1/Th2 and Th17/Treg cell immune imbalance. (December 2022) - Zhang, Beibei; Zeng, Mengnan; Zhang, Qinqin; Wang, Ru; Jia, Jufang; Cao, Bing; Liu, Meng; Guo, Pengli; Zhang, Yuhan; Zheng, Xiaoke; Feng, Weisheng
Abstract: Aims: This study aimed to investigate the anti-asthma effects of Ephedrae Herba polysaccharides (PE) and possible mechanisms related to immune inflammatory response. Methods: An asthma model was established in rats using ovalbumin (OVA). Seventy rats were randomly assigned to five groups: control, model, dexamethasone (DEX, 0.075 mg/kg), low dose polysaccharides (LPE, 137.71 mg/kg) and high dose polysaccharides (HPE, 275.42 mg/kg). The cough and asthma were used to evaluate the basic state of asthmatic rats. Histological studies were evaluated by hematoxylin and eosin (H&E), Masson, and periodic acid-schiff (PAS) staining. The levels of interferon-γ (IFN-γ), interleukin (IL)-4, immunoglobulin E (IgE), tumor necrosis factor α (TNF-α), and IL-17A in bronchoalveolar lavage fluid (BALF), and the levels of transforming growth factor β1 (TGF-β1), IL-6, and IL-10 in serum were detected by enzyme-linked immunosorbent assay (ELISA). The mRNA levels of Ifn-γ, Il-4, Tgf-β1, Il-6, Il-10, Tnf-α, Il-13, and Il-17a were evaluated by quantitative real-time reverse transcription (qRT)-PCR. The dendritic cell (DCs), T helper cell (Th), natural killer cell (NK), regulatory T cell (Treg), and Th17 cells in blood, the lymphocytes, macrophages and neutrophils in spleen, and cell apoptosis and reactive oxygen species (ROS) in lung were analysed by flow cytometry (FCM). Immunohistochemistry (IHC) was used to stain DCs (CD11c +, CD86 +, and CD80 + ), macrophages (CD68 + ), and neutrophils (MPO + ) in the spleen and lung. The protein levels of IL-17A, CD11c, CD86, and CD80 in lung were measured by western blot. Results: Our study demonstrated that PE could effectively improve the symptoms of asthmatic rats, ameliorate the lung pathological injury, inhibit inflammation, apoptosis and oxidative stress, regulate the levels of macrophages, neutrophils, DCs, NK, Thc, Treg and Th17 cells. Conclusion: PE could collectively inhibit the inflammation, apoptosis and ROS in asthma rats induced by OVA via regulating Th1/Th2 and Th17/Treg cell immune imbalance. Graphical Abstract: PE has a protective effect on OVA-induced asthma in rats, which could mitigate OVA induced asthma by inhibiting inflammation via regulating Th1/Th2 and Th17/Treg cell immune imbalance, which might be a useful medical strategy for treating asthma. ga1 Highlights: This paper is the first to explore the intervention effect and mechanism of polysaccharides in Ephedrae Herba on OVA-induced allergic asthma. Ephedrae Herba polysaccharides may treat OVA-induced allergic asthma by modulating inflammation and immunity.